Determinants Of Learning Autonomy Practices Among Gifted Students In Jeddah Saudi Arabia - Alqahtani, Wogaian Habib W (2021)
The present study aims to determine the use of learning autonomy among the gifted students in Saudi Arabia as well as the influence of the determinants on learners’ use of learning autonomy. Learning autonomy is a goal in gifted education to allow gifted students to become autonomous learners. Number of factors have been hypothesised to influence the use of learning autonomy from the learners’ perspectives. These factors are learners’ awareness, learners’ motivation, teachers’ role, and peers’ influence.